Lecturers’ Use of Body Language at Jadara University from the Students’ Point of View - Maberah, Shooroq (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to identify the degree to which lecturers at Jadara University effectively use body language from the students’ point of view. It also attempts to investigate whether body language skills differ according to a few variables. Methods: The study has a descriptive and analytical approach. (793) male and female students were randomly selected, and a questionnaire of (25) items was used after verifying its validity and reliability. Results: The results of the study show that lectures’ body language skills at Jadara University are average, with an arithmetic mean of (3.41). The results also reveal that the skills related to appearance, posture, and proximity as well as those related to head movement and facial expressions rank first and second with a high degree of importance whereas voice-related skills rank last with a moderate degree. Moreover, the study shows that there are no statistically significant differences at the significance level (α = 0.05) due to variables like gender, academic year, or academic program. Conclusions: Based on the results, the study proposes several recommendations. It mainly calls for offering specialized training courses addressing lecturers’ body language in the humanities and the scientific colleges. These courses should teach lecturers the most important skills and strategies which facilitate university education, as developing body language (as a non-verbal method of communication) helps in delivering information clearly and effectively.